Crystal Structure of the 65-Kilodalton Heat Shock Protein, Chaperonin 60.2, of Mycobacterium tuberculosis - Qamra, Rohini (American Society for Microbiology, 2004)
Chaperonin 60s are a ubiquitous class of proteins that promote folding and assembly of other cellular polypeptides in an ATP-dependent manner. The oligomeric state of chaperonin 60s has been shown to be crucial to their role as molecular chaperones. Chaperonin 60s are also known to be important stimulators of the immune system. Mycobacterium tuberculosis possesses a duplicate set of chaperonin 60s, both of which have been shown to be potent cytokine stimulators. The M. tuberculosis chaperonin 60s are present in the extracellular milieu at concentrations that are extremely low for the formation of an oligomer. Here we present the crystal structure of one of the chaperonin 60s of M. tuberculosis, also called Hsp65 or chaperonin 60.2, at 3.2-Å resolution. We were able to crystallize the protein in its dimeric state. The unusual dimerization of the protein leads to exposure of certain hydrophobic patches on the surface of the protein, and we hypothesize that this might have relevance in binding to immunogenic peptides, as it does in the eukaryotic homologs.